PSEUDO-3D SEISMIC SURVEY AT JEPON-01 WELL AREA, BLORA, CENTRAL JAVA - PANJI SAKTI (NIM: 22315021), THOMAS
Carbon Capture and Storage (CCS) Pilot Project has been started since 2012 located in Blora Regency, Central Java. Jepon-01 well has been selected as a candidate of injection well. The final processing stage of 2D seismic data from the previous study has been able to model Top of Ngrayong Formation in area surrounding Jepon-01 well. However, the model still has many uncertainties because this only a group of 2D seismic sections which distance of each line is far one another, so the interpretation result gives the subsurface model that contains a lot of interpolation. Further survey is needed to revise the subsurface model and furthermore as a reference for CCS monitoring. There are many operational constraints when conducting a survey in this site in the form of forest. Dynamites are not allowed and the restrictiveness of recording systems. Vibroseis is used as a substitution, that can only access wide roads. Pseudo-3D seismic acquisition is chosen considering the operational constraints in the field. The design of pseudo-3D seismic survey is unlike 3D seismic acquisition in general. Source and receiver lines are not orthogonal and irregular due to the restrictiveness of access path, but still get the fold distribution like 3D seismic acquisition. The data obtained from this survey contains information of offset and fold distribution which are spreaded unevenly. The data also shows that ground roll dominating that is affected of using surface source. Furthermore, guided waves arises due to a high contrast of layers near the surface. To eliminate predominance of the noise, predictive deconvolution used to attenuate guided waves and Surface Wave Noise Attenuation (SWNA) to attenuate ground rolls. Both techniques successfully attenuate the noise even with irregular offset. Stacks from this pseudo-3D seismic data is able to show a more convincing structural model on the area. The form of anticline structure is evident on two-way time of 350-500 ms, 550-700 ms, and 750-900 ms. Thus, it can be seen from the stack section that position Jepon-01 well is on the top of anticline.